2021
DOI: 10.1007/s00253-021-11551-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of thermostable sucrose phosphorylase by semi-rational design for efficient biosynthesis of alpha-D-glucosylglycerol

Abstract: Sucrose phosphorylase (SPase) can specifically catalyze transglycosylation reactions and can be used to enzymatically synthesize α-D-glycosides. However, the low thermostability of SPase has been a bottleneck for its industrial application. In this study, a SPase gene from Leuconostoc mesenteroides ATCC 12,291 (LmSPase) was synthesized with optimized codons and overexpressed successfully in Escherichia coli. A semi-rational design strategy that combined the FireProt (a web server designing thermostable protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…While others have reported that mutations that promote desired enzyme function often occur near the active site, , this work provides examples of productive mutations rationally selected from an allosteric ligand binding site. In line with our observations, small molecule metabolite pathways are rich in examples of enzymes that show altered substrate recognition due to allosteric ligand binding. Additionally, some kinases and proteases show different substrate preferences after modification of a distal site. , Since we found that homologous allosteric modification does not produce identical results in all Gram-negative RmlA proteins, it would be interesting to see how similar changes affect other bacterial nucleotidyltransferases regulated through feedback inhibition. ,, The findings described here will help inform future studies aimed at modulating cellular NDP-sugar pathways, perhaps through the use of nucleotidyltransferase mutant strains for the discovery of synthetic allosteric inhibitors of bacterial glycoconjugate precursors.…”
supporting
confidence: 74%
“…While others have reported that mutations that promote desired enzyme function often occur near the active site, , this work provides examples of productive mutations rationally selected from an allosteric ligand binding site. In line with our observations, small molecule metabolite pathways are rich in examples of enzymes that show altered substrate recognition due to allosteric ligand binding. Additionally, some kinases and proteases show different substrate preferences after modification of a distal site. , Since we found that homologous allosteric modification does not produce identical results in all Gram-negative RmlA proteins, it would be interesting to see how similar changes affect other bacterial nucleotidyltransferases regulated through feedback inhibition. ,, The findings described here will help inform future studies aimed at modulating cellular NDP-sugar pathways, perhaps through the use of nucleotidyltransferase mutant strains for the discovery of synthetic allosteric inhibitors of bacterial glycoconjugate precursors.…”
supporting
confidence: 74%
“…The decreased R g and SASA values of D172W/E207A suggested that these mutations resulted in a more tightly packed structure. The root-mean-square fluctuations (rmsf) values reflect the possibility for the movement of each amino acid in a protein, with larger rmsf values reflecting more degrees of freedom for that residue than those with smaller ones . Analysis of the RMSF plots generated based on MD simulations at 330 K (Figure S3) showed that most parts of the mutant is similar to the wild type.…”
Section: Resultsmentioning
confidence: 99%
“…The root-mean-square fluctuations (rmsf) values reflect the possibility for the movement of each amino acid in a protein, with larger rmsf values reflecting more degrees of freedom for that residue than those with smaller ones. 47 Analysis of the RMSF plots generated based on MD simulations at 330 K (Figure S3) showed that most parts of the mutant is similar to the wild type. Some changes between the wild type and mutant can be observed; in Chain A, compared to the wild type, residues 103−106, 111−127, 165−175, 202− 205, and 224−226 from mutants had lower RMSF values (Figure S3A); In chain B, residues 124−130, 170−187, 193− 205, and 296−321 had higher RMSF values of wild type than those of mutants (Figure S3B).…”
Section: Molecular Dynamic Analysis Of Wild Type and Mutant Blasnasesmentioning
confidence: 99%
“…Improving thermostability may decrease the enzyme activity because it could change the flexibility of the structure ( Xu et al, 2020 ). But, there are cases in which the thermostability was improved and the enzyme activity was increased by using FireProt ( Cheng et al, 2020 ; Xia et al, 2021 ). Protein analysis tools such as Rate4Site, FoldX, and Rosetta design were assembled to offer a reliable design of stable multiple-point mutants in FireProt ( Musil et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%